e-Klinik: Prototipe Sistem Layanan Klinik Gigi di Masa Pandemi Covid 19 - Sidik, Rangga; Fadhlurrahman, Muhammad Alfi (PETIR, 2022)
The implementation of health protocols during the Covid-19 pandemic had an impact on health service activities in dental clinics. Arrangements to keep distance and avoid crowds are important points in the implementation of dental health services for the community. The e-clinic system provides an alternative solution to assist dental health service workers in carrying out the administrative process and for doctors who diagnose patients through the use of web technology. This study made with the aim of analyzing and designing an e-clinic system to help dental clinic services during the Covid-9 pandemic. To get research results that suit its needs, the case study method is used with the application of prototype system development through an object-oriented systems approach. Modeling uses UML (unified modeling language) tools and testing is done using a black box. E-clinic models and system prototypes are the results of research conducted. The e-clinic system that was built is expected to make it easy for the community to get dental health services in clinics by implementing well-maintained health protocols.